Magnetic shepherding of nanocatalysts through hierarchically-assembled Fe-filled CNTs hybrid - Melchionna, Michele; Beltram, Alessandro; Stopin, Antoine; Montini, Tiziano; Lodge, Rhys W; Khlobystov, Andrei N.; Bonifazi, Davide; Prato, Maurizio; Fornasiero, Paolo (Elsevier, 2018)
Mechanically robust, chemically stable and electronically active carbon nanotubes (CNTs) are widely used as supports in catalysis. Synergistic effects between CNT and the active phase critically depend on the homogeneity of the carbon/inorganic interface, whose assembly is difficult to achieve without admixtures of free-standing inorganic matrix. Here we show that Fe-filled CNTs, employed as nanocatalyst supports, allow a facile preparation of highly pure and uniform CNT/nanocatalyst materials, by taking advantage of magnetic separation from poorly-defined components (e.g. aggregates of inorganic nanocatalysts). The higher homogeneity translates into higher catalytic activity in two industrially important processes: the photocatalytic hydrogen production and the water-gas shift reaction, WGSR (increase of ∼48% activity for the former and up to ∼45% for the latter as compared to catalysts isolated by standard filtration). In addition, the magnetic Fe core in the nanotubes enables effective separation and re-use of the nanocatalyst without loss of activity. This study demonstrates significant potential of magnetic CNTs as next generation of sustainable catalyst supports that can improve production of hydrogen and reduce the use of precious metals.